Study on mechanical and shielding properties of barite colemanite concrete - Safwan, Shalbi; Norazlianie, Sazali; Muhammad Aliff Ashraff, Rosdi; Faridah, Mohamad Idris (IOP Publishing, 2021)
Natural and artificial mineral additives have been frequently used for improving the physical, mechanical and radiation shielding properties of concrete in recent years. However, it was found that the mechanical properties, including hardness, tensile strength and elongation at break, of these radiation shielding blocks were reduced with increasing of the amount of radiation shielding substance mixed in the radiation shielding In this study, the mechanical and shielding properties of concrete mix with barite and colemanite was use in order to produce optimize shielding for Boron Neutron Capture Therapy at the thermal column of Malaysia research reactor. The barite colemanite concrete formulations are based on ASTM standard and each sample was tested with both mechanical and radiation testing. In mechanical testing, the slump test, ultrasonic pulse velocity test and compressive strength test. For instance, the shielding properties of barite colemanite concrete was tested using neutron test using small angle neutron microscopy (SANS) and gamma test using 60Co. The significance of mechanical and shielding test for barite colemanite concrete beneficial for the production of optimize use of barite and colemanite in concrete for high mechanical and high shielding properties for BNCT shielding purpose.